The Mod 2 Kauffman Bracket Skein Module of Thickened Torus (Communications in Mathematical Research, 2020)
Framed links in thickened torus are studied. We define the mod 2 Kauffman bracket skein module of thickened torus and give an expression of a framed linkin this module. From this expression we propose a new ambient isotopic invariant offramed links.
Keywords: framed link; thickened torus; mod 2 Kauffman bracket skein module